Degradation mechanism of AlGaN/GaN HEMTs during high temperature operation stress. (15th December 2017) - Chen, Y Q; Liao, X Y; Zeng, C; Peng, C; Liu, Y; Li, R G; En, Y F; Huang, Y
Abstract: The degradation behavior and its physical mechanism of AlGaN/GaN high electron mobility transistors (HEMTs) during high temperature operation (HTO) stress were investigated in this paper. The results show that the gate leakage current of AlGaN/GaN HEMTs after 1000 h HTO stress is two orders of magnitude larger than that of the fresh ones. The maximum transconductance of the AlGaN/GaN HEMTs obviously decreases from 0.31 to 0.21 s after 1000 h HTO stress, which indicates the gate degraded seriously. The mechanism for the gate degradation could be attributed to the Au diffusion that degrades the barrier. Moreover, the output characteristics are also deteriorated seriously, and the maximum variation of drain-to-source current is up to 119 mA under the conditions of gate-to-source voltage of 0 V and drain-to-source voltage of 5 V. The reason for the deterioration of output characteristics could be attributed to two mechanisms of gate degradation and structural damage such as pit-like, crack-like damages. The results may be useful in the design and application of AlGaN/GaN HEMTs.